1995
DOI: 10.1515/jpme.1995.23.1-2.99
|View full text |Cite
|
Sign up to set email alerts
|

Does recombinant human erythropoietin not only treat anemia but reduce postpartum (emotional) distress as well?

Abstract: Based on the established rhEPO treatment of anemia in endstage renal failure, which results in improved quality of life, and on the clinical observation that patients with postpartum anemia treated with rhEPO seemed to gain a more stable mood, we inferred that there is a beneficial side-effect of rhEPO on postpartum blues. The aim of this study was to test the hypotheses 1) that postpartum anemia aggravates, and 2) that treatment of postpartum anemia with rhEPO reduces maternity blues. The results show that on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 12 publications
1
9
0
1
Order By: Relevance
“…These negative findings are similar to results in one other large observational study [12] but differ from several studies that found an association [8, 1315]. There are no obvious or consistent differences between our study and, previous ones in study design, timing, and measures of iron status or PPD.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These negative findings are similar to results in one other large observational study [12] but differ from several studies that found an association [8, 1315]. There are no obvious or consistent differences between our study and, previous ones in study design, timing, and measures of iron status or PPD.…”
Section: Discussionsupporting
confidence: 83%
“…One of the earliest studies reported that low Hb was associated with such postnatal symptoms as low energy, faintness/dizziness, painful perineal sutures, and tingling of fingers and toes but not with PPD [12]. In contrast, several subsequent studies found that anemia and/or iron deficiency were associated with increased symptoms of postpartum blues and depression [8, 1315]. Although postpartum depression was assessed in most of these studies by the Edinburgh Postnatal Depression Scale (EPDS) [16], differences in iron measures make direct comparisons difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with postpartum anaemia show more symptoms on the so called symptom checklist SCL-90-R, more symptoms of 'maternity blues' and a reduced sense of well-being compared to nonanaemic patients [45,46]. Effective treatment of anaemia reduces cardiovascular distress and the risk for affective disorders.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, short-term (5 days) EPO vs. placebo treatment of anemic women showed no effect on postpartum blues (Meyer et al 1995). Until recently, the beneficial effects of EPO on mood and cognition were therefore simply attributed to reversal of patients' anemic state with longterm EPO treatment (Jelkmann 1992;Pickett et al 1999).…”
Section: Effects Of Epo In Human Populationsmentioning
confidence: 99%